2013
DOI: 10.1108/00400911311294924
|View full text |Cite
|
Sign up to set email alerts
|

Gaming across cultures: experimenting with alternate pedagogies

Abstract: PurposeHigher education is influenced, to an increasing extent, by changing student demographics. This requires educators to design and deliver learning systems which will enhance students’ learning experience with innovative, real world and engaging resources. The authors predict that transformations in the learning systems will increase as higher learning institutions seek to add educational value. The authors maintain that current pedagogies in cross‐cultural education are insufficiently adapted to student … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…The study by Balan and Metcalfe (2012) identified three techniques particularly effective for student engagement, namely, team-based learning, poster plan, and small business awards. Some scholars in the Asia Pacific focused on a specific pedagogy to discuss “how” this teaching technique impacts on or is implemented for effective learning, such as work-based learning (Gilbert, 2012; Huq and Gilbert, 2013), games (Pillay and James, 2013; Shankar, 2016), or case study (Chowdhary and Prakash, 2010). In addition, by briefly addressing teaching methods, some papers aimed to understand other EE issues regarding learner-centered approach to advance the learning environment (Jones, 2010) and foster students’ innovation and proactiveness (Prakash et al , 2015), team-based activities to examining a student’s psychological state (Man and Farquharson, 2015), and passive/active methods to increase entrepreneurial intention (Ruswanti, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…The study by Balan and Metcalfe (2012) identified three techniques particularly effective for student engagement, namely, team-based learning, poster plan, and small business awards. Some scholars in the Asia Pacific focused on a specific pedagogy to discuss “how” this teaching technique impacts on or is implemented for effective learning, such as work-based learning (Gilbert, 2012; Huq and Gilbert, 2013), games (Pillay and James, 2013; Shankar, 2016), or case study (Chowdhary and Prakash, 2010). In addition, by briefly addressing teaching methods, some papers aimed to understand other EE issues regarding learner-centered approach to advance the learning environment (Jones, 2010) and foster students’ innovation and proactiveness (Prakash et al , 2015), team-based activities to examining a student’s psychological state (Man and Farquharson, 2015), and passive/active methods to increase entrepreneurial intention (Ruswanti, 2016a).…”
Section: Discussionmentioning
confidence: 99%
“…The role of culture in online learning The higher education landscape is becoming increasingly heterogeneous in terms of the demographic composition (Pillay and James, 2012). Hence, we argue that the pervasive influence of culture should be regarded as a significant concern in the design of technology-enhanced learning systems.…”
Section: Introductionmentioning
confidence: 99%
“…Lending further credibility to the case for group working as an effective pedagogical technique for university students are scholars such as Pillay and James (2013, 2014), whose research highlights the various benefits of face-to-face learning that are wholly applicable to the context of students working in groups within a common physical space. A few of these benefits include interpersonal skills, ability to use humor, interaction management, relationship building and cultural empathy, all of which contribute toward the development of intercultural competence (Pillay and James, 2015), which along with teamwork and problem solving are the key traits required of 21st-century managers and for students seeking employment upon completion of their formal education.…”
Section: Literature Reviewmentioning
confidence: 99%